Cross-Talks Between Macro- and Micronutrient Uptake and Signaling in Plants - Fan, Xiaoning; Zhou, Xiaoqin; Chen, Hui; Tang, Ming; Xie, Xianan (Frontiers in Plant Science, 2021)
In nature, land plants as sessile organisms are faced with multiple nutrient stresses that often occur simultaneously in soil. Nitrogen (N), phosphorus (P), sulfur (S), zinc (Zn), and iron (Fe) are five of the essential nutrients that affect plant growth and health. Although these minerals are relatively inaccessible to plants due to their low solubility and relative immobilization, plants have adopted coping mechanisms for survival under multiple nutrient stress conditions. The double interactions between N, Pi, S, Zn, and Fe have long been recognized in plants at the physiological level. However, the molecular mechanisms and signaling pathways underlying these cross-talks in plants remain poorly understood. This review preliminarily examined recent progress and current knowledge of the biochemical and physiological interactions between macro- and micro-mineral nutrients in plants and aimed to focus on the cross-talks between N, Pi, S, Zn, and Fe uptake and homeostasis in plants. More importantly, we further reviewed current studies on the molecular mechanisms underlying the cross-talks between N, Pi, S, Zn, and Fe homeostasis to better understand how these nutrient interactions affect the mineral uptake and signaling in plants. This review serves as a basis for further studies on multiple nutrient stress signaling in plants. Overall, the development of an integrative study of multiple nutrient signaling cross-talks in plants will be of important biological significance and crucial to sustainable agriculture.